Multicriteria decision-making analysis based methodology for predicting carbonate rocks' uniaxial compressive strength (2012)
ABSTRACTUniaxial compressive strength (UCS) deals with materials' to ability to withstand axially-directed pushing forces and especially considered to be rock materials' most important mechanical properties. However, the UCS test is an expensive, very time-consuming test to perform in the laboratory and requires high-quality core samples having regular geometry. Empirical equations were thus proposed for predicting UCS as a function of rocks' index properties. Analytical hierarchy process and multiple regression analysis based methodology were used (as opposed to traditional linear regression methods) on data-sets obtained from carbonate rocks in NE Turkey. Limestone samples ranging from Devonian to late Cretaceous ages were chosen; travertine-onyx samples were selected from morphological environments considering their surface environmental conditions Test results from experiments carried out on about 250 carbonate rock samples were used in deriving the model. While the hierarchy model focused on determining the most important index properties affecting on UCS, regression analysis established meaningful relationships between UCS and index properties; 0. 85 and 0. 83 positive coefficient correlations between the variables were determined by regression analysis. The methodology provided an appropriate alternative to quantitative estimation of UCS and avoided the need for tedious and time consuming laboratory testingRESUMENLa resistencia a la compresión uniaxial (RCU) trata con la capacidad de los materiales para soportar fuerzas empujantes dirigidas axialmente y, especialmente, es considerada ser uno de las más importantes propiedades mecánicas de los materiales rocosos. Sin embargo, una prueba de RCU es costosa, lleva mucho tiempo para hacerlo en el laboratorio y requiere muestras de núcleos de alta calidad que tienen una geometría regular.Por lo tanto, ecuaciones empíricas fueron propuestas para la predicción de RCU como una función de las propiedades índice de las rocas. Las metodologías de proceso analítico jerárquico (PAJ) y análisis de regresión múltiple fueron utilizados (en vez de los métodos tradicionales de regresión lineal) en conjuntos de datos obtenidos de las rocas carbonatadas en el noreste de Turquía Muestras de rocas calizas que van desde el Devónico hasta finales del Cretácico fueron escogidas; muestras de travertino y ónix fueron seleccionadas de ambientes morfológicos teniendo en cuenta sus condiciones ambientales de superficie.Los resultados de los experimentos llevados a cabo en alrededor de 250 muestras de rocas carbonatadas fueron utilizados para derivar un modelo Mientras que el modelo de jerarquía se centró en determinar las propiedades índice más importantes afectados por la RCU, el análisis de regresión establece relaciones significativas entre la RCU y las propiedades del índice; coeficientes de correlación positivas de 0,85 y 0,83 fueron determinadas por análisis de regresión entre las variables La metodología proporciona una alternativa adecuada para la estimación cuantitativa de la RCU y evita la necesidad de realizar pruebas del laboratorio las cuales son tediosas y dispendiosas